2005
DOI: 10.5326/0410056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Normograde and Retrograde Intramedullary Pinning of Feline Tibias

Abstract: This study evaluated the effects of normograde and retrograde intramedullary pinning of mid-diaphyseal fractures of the feline tibia on the anatomical structures of the stifle joint. Using the paired pelvic limbs from five mature feline cadavers, a transverse, mid-diaphyseal osteotomy was performed, and each tibia was pinned in a normograde or retrograde fashion. The stifle joints were examined to determine the pin exit site and measure the distance from the exit site to pertinent anatomical structures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…14,15 A higher incidence of trauma to the stifle joint has been demonstrated in dogs with retrograde intramedullary pin placement compared with normograde pin placement, 16 and a study in cats showed penetration of the PL in all cases of retrograde intramedullary pin placement in the tibia. 17 The single case of iatrogenic RPL in this study supports both the necessity for accurate tibial intramedullary pin placement and the recommendation for normograde pin placement to treat feline tibial fractures.…”
Section: Discussionsupporting
confidence: 68%
“…14,15 A higher incidence of trauma to the stifle joint has been demonstrated in dogs with retrograde intramedullary pin placement compared with normograde pin placement, 16 and a study in cats showed penetration of the PL in all cases of retrograde intramedullary pin placement in the tibia. 17 The single case of iatrogenic RPL in this study supports both the necessity for accurate tibial intramedullary pin placement and the recommendation for normograde pin placement to treat feline tibial fractures.…”
Section: Discussionsupporting
confidence: 68%
“…Intramedullary pins should always be inserted in a normograde fashion into the tibia because retrograde pinning in cats invariably results in penetration of the patellar tendon (6). Intramedullary pins should always be inserted in a normograde fashion into the tibia because retrograde pinning in cats invariably results in penetration of the patellar tendon (6).…”
Section: Intramedullary Pinningmentioning
confidence: 99%